The Relationship of Physical Activity to Students' Creative Thinking Ability - Yudi Dwi Saputra; Nurdian Ahmad (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
This study aims to determine the relationship between physical activity and students' creative thinking abilities. This type of research uses the correlation method and is a population study because it uses all tenth-grade students of SMK Khoiriyah Jombang, totaling 58 students. Data collection techniques using IPAQ (International Physical Activity Questionnaire) questionnaire instruments and the Student Creative Thinking Ability Questionnaire The results of data analysis with a coefficient interval of 0.223 for the relationship of physical activity with the ability to think creatively show that the two variables are interrelated with the interpretation of the correlation coefficient of value (r) of the independent variable (physical activity) and the dependent variable (ability to think creatively), even though the level of relationship is low.